2020
DOI: 10.7717/peerj.9412
|View full text |Cite
|
Sign up to set email alerts
|

Using Bumble Bee Watch to investigate the accuracy and perception of bumble bee (Bombus spp.) identification by community scientists

Abstract: Community science programs provide an opportunity to gather scientific data to inform conservation policy and management. This study examines the accuracy of community science identifications submitted to the North American Bumble Bee Watch program on a per species level and as compared to each species’ conservation status, as well as users (members of the public) and experts (those with expertise in the field of bumble bee biology) perceived ease of species identification. Photos of bumble bees (Hymenoptera: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(22 citation statements)
references
References 57 publications
0
22
0
Order By: Relevance
“…With programs such as BeeSpotter (beespotter.org), Bumble Bee Watch (BBW; bumblebeewatch.org), iNaturalist (inaturalist.org), and the Wisconsin Bumble Bee Brigade (WBBB; wiatri.net/inventory/bbb), users can contribute to national and regional databases by uploading georeferenced images of bumble bees and providing preliminary identifications, which are then verified by experts or community sourced. This verification step is important because user-submitted identifications to WBBB and BBW agree with experts only 73 and 53 percent of the time, respectively 15 , 16 . If not properly verified, such erroneous data could have serious negative consequences for pollinator conservation.…”
Section: Introductionmentioning
confidence: 99%
“…With programs such as BeeSpotter (beespotter.org), Bumble Bee Watch (BBW; bumblebeewatch.org), iNaturalist (inaturalist.org), and the Wisconsin Bumble Bee Brigade (WBBB; wiatri.net/inventory/bbb), users can contribute to national and regional databases by uploading georeferenced images of bumble bees and providing preliminary identifications, which are then verified by experts or community sourced. This verification step is important because user-submitted identifications to WBBB and BBW agree with experts only 73 and 53 percent of the time, respectively 15 , 16 . If not properly verified, such erroneous data could have serious negative consequences for pollinator conservation.…”
Section: Introductionmentioning
confidence: 99%
“…Goulson et al [ 49 ] point out that community science surveys are often limited by the taxonomic skills of the observers, particularly for bee species that are difficult or impossible to identify in the field because of cryptic coloration. MacPhail et al [ 50 ] reported that 46.3% of B. vagans , 38.6% of B. sandersoni , and 86.4% of B. perplexus were correctly identified from photos of Bombus by project designated expert taxonomists, or they were placed into a “two-striped species group” when the photos were ambiguous. Richardson et al [ 13 ] found that they could reliably make a species determination from 68% of photographs submitted by participants in the Vermont Bumble Bee Atlas.…”
Section: Discussionmentioning
confidence: 99%
“…Despite these oft-cited limitations, community science is an effective tool for gathering data over a large geographic scale (Deguines et al 2016) or detecting relatively rare events such as bee nesting (Lye et al 2012). Further, community science can provide more reliable identifications when observations are validated by multiple expert taxonomists (Le Féon et al 2016;Falk et al 2019;MacPhail et al 2020b). In this study, we addressed this issue by using embedded taxonomic experts to confirm bee identifications and ensuring appropriately conservative levels of taxonomic resolution (often subgenus-level) with species identifications made conservatively where warranted.…”
Section: Comparing Literature and Community Sciencementioning
confidence: 99%